Report of the FAO regional workshop on the elaboration of National Plans of action to prevent, deter and eliminate illegal, unreported and unregulated fishing: Southeast Asia subregion. Penang (Malaysia). 10-14 Oct 2004 - FAO, Rome (Italy) (Rome (Italy), 2005)
Sumario (En)
no. 757
Keywords: PESCA; PRACTICAS ILEGALES; RECURSOS PESQUEROS; ORDENACION DE RECURSOS; PROYECTOS DE DESARROLLO